1983
DOI: 10.1073/pnas.80.14.4334
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester inhibits furosemide-sensitive potassium transport in BALB/c 3T3 preadipose cells.

Abstract: The tumor promoter phorbol 12-myristate 13-acetate (PMA) rapidly decreased the rate of "Rb+ uptake into BALB/c 3T3 preadipose cells. The component of total 86Rb+ influx affected by PMA is insensitive to ouabain but sensitive to the diuretic furosemide. Experiments designed to investigate the characteristics of the K+ transport system sensitive to PMA revealed that: (i) 86Rb+ uptake is highly dependent on external Na+, (ii) "Rb+ uptake is highly dependent on external ClP, (iii) 22Na+ uptake is dependent on exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
2

Year Published

1985
1985
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 27 publications
4
29
2
Order By: Relevance
“…Clues to the answer to this important question may lie in the similarities of early cellular responses to two diverse stimuli: phorbol ester and osmotic stress, especially hyperosmolar stress. Both stimuli alter net ion fluxes [1,18], cause rapid cell shrinkage followed by subsequent recovery, and stimulate phosphorylation of several proteins [1,. In fact, Lytle and Forbush [22] have shown that the same shark NKCCl used in these studies is phosphorylated on two threonine residues by hyperosmolar conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clues to the answer to this important question may lie in the similarities of early cellular responses to two diverse stimuli: phorbol ester and osmotic stress, especially hyperosmolar stress. Both stimuli alter net ion fluxes [1,18], cause rapid cell shrinkage followed by subsequent recovery, and stimulate phosphorylation of several proteins [1,. In fact, Lytle and Forbush [22] have shown that the same shark NKCCl used in these studies is phosphorylated on two threonine residues by hyperosmolar conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have developed circumstantial evidence that a membrane transporter, the Na/ K/Cl cotransporter (NKCCI), is a critical signal-generating substrate for PKC in BALB/c 3T3 cells [1][2][3][4]. The activity of this protein, which transports Na+, K' , and C1-in a bidirectional, electroneutral, and diuretic-(i.e., bumetanide, furosemide) sensitive manner in many cell types, is rapidly inhibited by phorbol-ester treatment [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular content of Na+ and K+ is mainly regulated by the Na+/K+ ATPase, and in some cases the Na+/H+, antiport in cell membranes, whose activities have been shown to be activated by phorbol ester tumor promoters and growth factors such as platelet-derived growth factor [6,22,37,38,44,56,60]. There is evidence that Na+/K+ ATPase activation is linked to the enhancement of cell growth and of TPA-mediated transformation in C3HIOT1/2 cells, and that a tumor promotion inhibitor, retinoic acid, inhibits TPA-mediated activation of the Na+/K+ ATPase in C3H10T1/2 [3].…”
Section: Regulation Of Cell Communication and Cell Growthmentioning
confidence: 99%
“…TPA and dther mitogens normally induce a rapid change in ion transport properties. One such TPA-modulatable system which is rapidly inhibited in 3T3 cells is the sodium-potassium-chloride transport system (14). The BALB/c 3T3 variant cell line A31T6E12A was isolated by seletting for a defect in this TPA-sensitive transport system (25).…”
mentioning
confidence: 99%